2017
DOI: 10.2147/nsa.s113030
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and cytocompatibility of potential cockle shell aragonite nanocrystals for osteoporosis therapy and hormonal delivery

Abstract: Calcium carbonate is a porous inorganic nanomaterial with huge potential in biomedical applications and controlled drug delivery. This study aimed at evaluating the physicochemical properties and in vitro efficacy and safety of cockle shell aragonite calcium carbonate nanocrystals (ANC) as a potential therapeutic and hormonal delivery vehicle for osteoporosis management. Free and human recombinant parathyroid hormone 1-34 (PTH 1-34)-loaded cockle shell aragonite calcium carbonate nanocrystals (PTH-ANC) were sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 36 publications
4
49
0
Order By: Relevance
“…There are different phases between scaffolds with and without the cockle shell powder. Jaji et al [2] and Lopez-Heredia et al [33] found similar results where the purity and crystallinity of CaCO 3 in the scaffolds were maintained even with the addition of other polymers. 2 a shows an amorphous structure where broad peaks appeared around 13.3°and 21.8°.…”
Section: Characterization Of Bone Scaffoldsmentioning
confidence: 65%
See 2 more Smart Citations
“…There are different phases between scaffolds with and without the cockle shell powder. Jaji et al [2] and Lopez-Heredia et al [33] found similar results where the purity and crystallinity of CaCO 3 in the scaffolds were maintained even with the addition of other polymers. 2 a shows an amorphous structure where broad peaks appeared around 13.3°and 21.8°.…”
Section: Characterization Of Bone Scaffoldsmentioning
confidence: 65%
“…The results also demonstrate that the purity of CaCO 3 in the scaffolds was not affected by the existence of SA. Jaji et al [2] and Lopez-Heredia et al [33] found similar results where the purity and crystallinity of CaCO 3 in the scaffolds were maintained even with the addition of other polymers. On the contrary, SA scaffold displayed bands around 3336, 1585, 1407, and 1025 cm -1 .…”
Section: Characterization Of Bone Scaffoldsmentioning
confidence: 65%
See 1 more Smart Citation
“…They can be produced using different types of biocompatible materials [5,6]. The use of nanoparticle-based drug carrier systems in the field of nanotechnology has become an area with a novel attention in the past few decades due to their unique and superior properties that enable functionalisation at both molecular and cellular levels [7][8][9][10][11][12][13][14]. Advanced novel drug delivery systems help to boost the efficacy of therapeutic drugs as well as minimising the rate of a drug's off targeted effects thereby preventing cytotoxicity to normal cells [8].…”
Section: Introductionmentioning
confidence: 99%
“…Cockle (Anadara granosa) with a Malaysian native name "kerang" belongs to the family of Cardiidae, which is a small, salt water edible clam that is popularly referred to as marine bivalve mollusc [11]. It is native to coastal regions of South East Asia (Malaysia, Thailand and Indonesia).…”
Section: Introductionmentioning
confidence: 99%